In vitro hypoglycemic effects and starch digestibility characteristics of wheat based composite functional flour for diabetics - Ahmed, Faiyaz (J Food Sci Technol, 2014)
The associations between chronic feeding of high level of soluble/insoluble fibers and low serum glucose levels have been well documented. In the present study, composite flours were formulated using psyllium, barley and oat at two different levels [WPOB-I = wheat flour (75 %), psyllium (5 %), oat (10 %) and barley (10 %), WPOB-II = wheat flour (60 %), psyllium (10 %), oat (15 %) and barley (15 %)]. Chapaties were prepared from all formulations and various starch fractions were analyzed using controlled enzymatic digestion. The digestibility characteristics were studied using amylolysis kinetics employing porcine pancreatic α-amylase in vitro. Results showed that both the variations (WPOB-I & WPOB-II) had acceptable sensory qualities and had significantly lower (p ≤ 0.05) values for total starch (TS), rapidly digestible starch (RDS), resistant starch (RS), starch digestibility index (SDI) and rapidly available glucose (RAG) compared to control. Between the two variations, WPOB-I showed better starch digestibility characteristics with significantly lower (p ≤ 0.05) starch digestibility index (SDI). In case of amylolysis kinetics, both the variations significantly (p ≤ 0.05) inhibited α-amylase as reflected by lower glucose diffusion and significantly higher (p ≤ 0.05) glucose dialysis retardation index (GDRI) compared to control. It is inferred that, consumption of the composite flours might be helpful in establishing stable blood glucose pattern due to the redistribution of nutritionally important starch fractions and inhibition of carbohydrate digestion in the gastrointestinal tract.